2021
DOI: 10.1049/mia2.12137
|View full text |Cite
|
Sign up to set email alerts
|

Automated optimization for broadband flat‐gain antenna designs with artificial neural network

Abstract: An automated optimization process for designing and optimising high-performance single microstrip antennas is presented. It consists of the successive use of two optimization methods, bottom-up optimization (BUO) and Bayesian optimization (BO), which are applied sequentially, resulting in electromagnetic (EM)-based artificial neural network modelling. The BUO method is applied for the initial design of the structure of the antennas whereas the BO approach is successively implemented to predict suitable dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…With respect to the authors' experience, AI methods can be used as platforms for constructing reported optimization methods and optimizing system's output specifications in an efficient way. Kouhalvandi et al in various research papers have proved this idea where ANNs and deep neural networks (DNNs) are used as platforms for optimizing power amplifiers (PAs) and antennas' output specifications using diverse multi‐objective optimization methods 56,261,283 . This idea leads to optimize complex systems in an automated environment without depending to any human's experience.…”
Section: Authors' Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the authors' experience, AI methods can be used as platforms for constructing reported optimization methods and optimizing system's output specifications in an efficient way. Kouhalvandi et al in various research papers have proved this idea where ANNs and deep neural networks (DNNs) are used as platforms for optimizing power amplifiers (PAs) and antennas' output specifications using diverse multi‐objective optimization methods 56,261,283 . This idea leads to optimize complex systems in an automated environment without depending to any human's experience.…”
Section: Authors' Outlookmentioning
confidence: 99%
“…Kouhalvandi et al in various research papers have proved this idea where ANNs and deep neural networks (DNNs) are used as platforms for optimizing power amplifiers (PAs) and antennas' output specifications using diverse multi-objective optimization methods. 56,261,283 This idea leads to optimize complex systems in an automated environment without depending to any human's experience.…”
Section: Authors' Outlookmentioning
confidence: 99%
“…They found the PSO-MANFIS model provided more accurate results than the GA-MANFIS model. Conversely, Mir et al [31] investigated an automated optimization procedure based on Bayesian-optimization (BO) and bottom-up-optimization (BUO) to design the MPA for broadband with high flat-gain features. The initial structure of the MPA is designed by the BUO approach while the BO process is applied to forecast appropriate dimensional parameters.…”
Section: Related Workmentioning
confidence: 99%
“…( 28)). Now, the other coordinates of the antenna radiators (i.e., p 1 , p 2 , p 3 , p 4 , and p 5 ) are obtained as per equations (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), which are found using the GSA-QPSO algorithm. Though, MATLAB is applied as the key development tool; where HFSS has been utilized to validate the performance of reflection coefficients and radiation characteristics.…”
Section: System Implementationmentioning
confidence: 99%
“…Due to the complexity of MIMO antennas, it is not straightforward to model and design these circuits, and optimization-based approaches are importantly required. Reported various optimization methods around radio frequency and antenna designs are particle swarm optimization [6,7], ant colony optimization [8,9], chicken swarm optimization [10], harmony search algorithm [11], and genetic algorithm [12]; however, when the design parameters are in a huge number these methods can not be successful and intelligent based optimization methods are required [13].…”
Section: Introductionmentioning
confidence: 99%